Significantly Low Levels of IgG Antibodies Against Oncogenic Merkel Cell Polyomavirus in Sera From Females Affected by Spontaneous Abortion - Mazziotta, Chiara; Pellielo, Giulia; Tognon, Mauro; Martini, Fernanda; Rotondo, John Charles (Frontiers in Microbiology, 2021)
Merkel cell polyomavirus (MCPyV) is a small DNA tumor virus being ubiquitous in humans. MCPyV establishes a clinically asymptomatic lifelong infection in healthy immunocompetent individuals. Viral infections are considered to be risk factors for spontaneous abortion (SA), which is the most common adverse complication of pregnancy. The role of MCPyV in SA remains undetermined. Herein, the impact of MCPyV infection in females affected by SA was investigated. Specifically, an indirect ELISA method with two linear synthetic peptides/mimotopes mimicking MCPyV antigens was used to investigate IgG antibodies against MCPyV in sera from 94 females affected by SA (mean [±SD] age 35±[6] years) and from 96 healthy females undergoing voluntary pregnancy interruption, (VI, mean [±SD] age 32±[7] years). MCPyV-seroprevalences and serological profiles were analysed. The overall prevalence of serum IgG antibodies against MCPyV was 34% (33/94) and 37.5% (36/96) in SA and VI females, respectively (P>0.05). Notably, serological profile analyses indicated lower optical densities (ODs) in females with SA compared to those undergoing VI (p<0.05), thus indicating a reduced IgG antibody response in SA females. Circulating IgGs were identified in sera from SA and VI females. Our immunological findings indicate that a relatively reduced fraction of pregnant females carry serum anti-MCPyV IgG antibodies, while the decrease in IgG antibody response to MCPyV in SA females may suggest that females experiencing abortive events are more susceptible to MCPyV infection.